AN ANATOMICAL STUDY OF THE LATEROTRIGEMINAL VENOUS SYSTEM - Simoes, S. (Gustav Fischer Verlag, 1993)
The middle cranial fossa of 100 cadavers were dissected under stereoscopic loupe in order to identify and systematize the venous vessels located along the lateral margin of the trigeminal cave. The author found that at the sensitive root and trigeminal ganglion level a dural venous canal was present in most individuals examined and that the upper side of this canal communicated with the superior petrosal sinus. However, at the level of the lateral border of the intracranial segment of the mandibular nerve, venous lacunae were found to prevail, and these lacunae communicated with several other venous formations in the peritrigeminal region. The author concludes that the venous vascularization of this area constitutes a major risk in surgical interventions made in the middle cranial fossa. In addition, it is a relevant factor in the hemodynamics of the intracranial circulation.
Keywords: TRIGEMINAL NERVE; TRIGEMINAL CAVE; VENOUS SINUSES; DURA MATER; VEINS